Genetic Identification of Shiga Toxin Encoding Gene from Cases of Multidrug Resistance (MDR) Escherichia coli Isolated from Raw Milk - R. Ansharieta; M. H. Effendi; H. Plumeriastuti (Faculty of Animal Science, Bogor Agricultural University, 2021)
Escherichia coli is one of bacteria which have resistant to three or more classes of antimicrobial agents. E. coli having resistant to three or more classes of antimicrobial drugs can be defined as multidrug-resistant (MDR) bacteria. The aim of the study was to evaluate the expression of Shiga toxin gen in MDR E. coli. A total of 250 raw milks samples were taken from dairy farms in Kediri, Probolinggo, Pasuruan, Blitar, and Batu Region, East Java Province, Indonesia. Each sample was cultured into enrichment media Brilliant Green Bile Lactose Broth and Eosin Methyllen blue agar, then identified with TSIA agar and IMVIC biochemistry test. Antibiotic sensitivity testing was done using Kirby-Bauer disc diffusion assay on medium Mueller-Hinton agar (Oxoid, CM0337). Antibiotics disks used were 30 µg of Tetracycline (Oxoid, CT0054), 10 µg of Streptomycin (Oxoid, CT0047), 30 µg of Chloramphenicol (Oxoid, CT0013), 5 µg of Trimethoprim (Oxoid, CT0057), and 30 µg of Aztreonam (Oxoid, CT0264). Isolate showing resistance to at least 3 antibiotics disk were then continued with PCR assay to identify Shiga toxin E. coli (STEC) encoding stx2 gene. The study was designed to evaluate the nucleotide analysis of STEC gene. The result showed that 6.25% (1/16) of STEC encoding gene was found in MDR E. coli. This report of molecular identification on the presence of STEC gene in MDR E. coli confirmed a wider spread of MDR E. coli that can threaten animal health and human health.